2016
DOI: 10.1002/ece3.2087
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear introgression without mitochondrial introgression in two turtle species exhibiting sex‐specific trophic differentiation

Abstract: Despite the presence of reproductive barriers between species, interspecific gene introgression has been documented in a range of natural systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 72 publications
0
7
0
Order By: Relevance
“…In the G. pseudogeographica species complex, of interest for us, a G. geographica X G. ouachitensis F1 hybrid female was apparently sterile (Vogt 2018) and there appears to be a decrease in fitness in G. geographica X G. pseudogeographica hybrid females (Freedberg and Myers 2012;Mitchell et al 2016), but there is no indication (so far) for any incompatibility between G. pseudogeographica and G. ouachitensis (Freedberg and Myers 2012;Vogt 2018 but also in Ploiești and Piteşti (Iftime and Iftime, pers. obs., 2020 -Fig.…”
Section: Fam Emydidaementioning
confidence: 99%
“…In the G. pseudogeographica species complex, of interest for us, a G. geographica X G. ouachitensis F1 hybrid female was apparently sterile (Vogt 2018) and there appears to be a decrease in fitness in G. geographica X G. pseudogeographica hybrid females (Freedberg and Myers 2012;Mitchell et al 2016), but there is no indication (so far) for any incompatibility between G. pseudogeographica and G. ouachitensis (Freedberg and Myers 2012;Vogt 2018 but also in Ploiești and Piteşti (Iftime and Iftime, pers. obs., 2020 -Fig.…”
Section: Fam Emydidaementioning
confidence: 99%
“…Despite these variations, recent studies suggest that hybridization is frequently observed in contact zones (Jiggins et al, 1996;Mallet, 2005). The genetic introgression can differentially involve mitochondrial and nuclear genomes (Dufresnes et al, 2015;Mitchell, Muehlbauer & Freedberg, 2016). Furthermore, genetic introgression can be asymmetric and occur preferentially in one of the two species in contact (Mallet, 2005;Dufresnes et al, 2015Dufresnes et al, , 2016.…”
Section: Introductionmentioning
confidence: 99%
“…In order to better understand parapatric distribution, it appears critical to focus on contact zones to examine possible hybridizations and genetic introgressions (Dufresnes et al, 2015). In this context, both mitochondrial and nuclear markers provide useful tools to detect potential barriers between species or quantify the amount and directionality of gene flow (Mitchell et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…With faster evolutionary rates, mitogenes are advantageous for studying relationships of crown groups, while nuclear genes offer abundant information in resolving relationships of deeper clades of a tree. Phylogenetic relationships inferred from nuclear DNA might be bias for taxa in which introgressive hybridization is common [ 70 ], while such interference decreases in mitogenomes if it is restricted to male introgression [ 71 ]. Secondly, different mitogenes can be discrepant in resolving relationships of species, for evolutionary rate varied through the whole mitogenome.…”
Section: Discussionmentioning
confidence: 99%